1995
DOI: 10.1002/qua.560560421
|View full text |Cite
|
Sign up to set email alerts
|

On the gradient expansion of the exchange energy within linear response theory and beyond

Abstract: -In the present work, we reexamined the gradient expansion of the exchange energy of an electron gas with a slowly varying charge density. We stay within the exchange-only approximation of Sharp, Horton, Talman, and Shadwick but go to second order in the deviation from the homogeneous limit. The coefficient of the lowest-order gradient correction is obtained analytically both for a bare and a screened Coulomb interaction-the former yielding the value previously obtained by Kleinman numerically and by Engel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…The problem does, for instance, not appear when Yukawa-screened Coulomb interactions are used. 38 The conclusion is that there is nothing wrong with the Kirzhnits method, or the nonlinear response theory derivation of the gradient expansion of the exchange hole presented here, but one has be aware that for Coulomb interactions the procedures of expanding correlation functions in terms of density gradients followed by integrations involving Coulomb potentials may not yield the same result as directly expanding the integrated quantity in terms of density gradients. For this reason the original GGA of Perdew and Wang 10 based on the gradient expansion of the exchange hole was later reparameterized 16,40 to accommodate the correct gradient coefficient for the exchange energy.…”
Section: B the Exchange Hole And Energymentioning
confidence: 86%
See 1 more Smart Citation
“…The problem does, for instance, not appear when Yukawa-screened Coulomb interactions are used. 38 The conclusion is that there is nothing wrong with the Kirzhnits method, or the nonlinear response theory derivation of the gradient expansion of the exchange hole presented here, but one has be aware that for Coulomb interactions the procedures of expanding correlation functions in terms of density gradients followed by integrations involving Coulomb potentials may not yield the same result as directly expanding the integrated quantity in terms of density gradients. For this reason the original GGA of Perdew and Wang 10 based on the gradient expansion of the exchange hole was later reparameterized 16,40 to accommodate the correct gradient coefficient for the exchange energy.…”
Section: B the Exchange Hole And Energymentioning
confidence: 86%
“…The coefficient B x is the same gradient coefficient as obtained by Gross and Dreizler 31 and earlier by Sham. 34 However, the correct analytic exchange gradient coefficient is known [35][36][37][38][39] to be a factor 10/7 larger. The reason for this discrepancy is clearly described by Svendsen and von Barth 38 who showed that the Coulomb interaction is too singular to allow for the interchange of the operations of integration and the expansion in wave vectors.…”
Section: B the Exchange Hole And Energymentioning
confidence: 99%
“…By a simultaneous study of the slowly-varying limit and the limit of low-order response, both the forms and the coefficients in front of different gradient corrections can be determined. 6 We will now investigate the possibility of modeling the exact exchange functional by retaining these forms, while using the coefficients as adjustable parameters.…”
Section: The Real-space Methodsmentioning
confidence: 99%
“…In previous work 6,7 we have argued that the electronic density of an atom is certainly not a linear perturbation of the homogeneous electron gas. We have also suggested that higher-degree gradients might be useful in attempts to model the true exchangecorrelation or exchange functionals.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate functionals were later constructed by parameterizing the Monte-Carlo calculations of Ceperley and Alder 16 and making sure that the high density limit of the correlation functional was reproduced. Further work on correlation functionals is that given by Langreth As is clear, the approach to developing functionals has been to start with the simplest functional given by the LDA, making gradient correction to it up the second order or the fourth order 21,22 and then demanding that the resulting functional satisfy exact conditions for them. The results have been that highly accurate energies can now be calculated using density functionals developed over the past two decades.…”
Section: Introductionmentioning
confidence: 99%